African Platyplectrus Ferrière (Hymenoptera: Eulophidae) from Kenya, with description of nine new species - Yefremova, Zoya A.; Copeland, Robert S. (Zootaxa, 2023)
Eleven species of Platyplectrus have been recorded from the Afrotropical region. Ch. Ferrière described nine species in 1941: two of them as Platyplectrus (P. capensis and P. ornatus) and seven under Euplectromorpha (Platyplectrus ausensis, P. brevicornis, P. kiambuensis, P. obscuratus, P. nitidiceps, P. striolata and Euplectromorpha variegata (not synonymized until the present paper)). Subsequently, P. meruensis was described by Delucchi (1962) and P. desertus by Yefremova (2008). To date, only one species, P. kiambuensis, has been recorded from Kenya. Recently, a wide-ranging survey and inventory project in Kenya raised this number to 18 species, nine of which are new and described herein: Platyplectrus albiclavatus sp. nov., P. kayaensis sp. nov., P. marenjeensis sp. nov., P. mrimaensis sp. nov., P. ngangaoensis sp. nov., P. nyambeneensis sp. nov., P. nyanzaensis sp. nov., P. pseudoornatus sp. nov., and P. pyrrhomaculatus sp. nov. Three species are redescribed: two for both sexes (P. meruensis, P. obscuratus) and one for females (P. ornatus). A new combination is proposed for Platyplectrus striolatus (Ferrière) from Euplectromorpha striolata Ferrière, 1941, and Euplectromorpha variegata Ferrière, 1941 is synonymized with Platyplectrus nigroflaveatus Yefremova, and the female is redescribed. A key to the genus Platyplectrus is provided for the 18 species found in Kenya.